Assessment of the Sensitivity and Specificity of Enzyme-Linked Immunosorbent Assay (ELISA) for the Detection of Mycobacterial Antibodies in Bovine Tuberculosis - Ritacco, Viviana (1987)
Fil: Ritacco, Viviana. Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET). Universidad de Lujan; Argentina.